2017
DOI: 10.18632/oncotarget.16671
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of the effects of simultaneous inhibition of GLUT-1 and HIF-1α by antisense oligodeoxynucleotides on the radiosensitivity of laryngeal carcinoma using micro 18F-FDG PET/CT

Abstract: PurposeHypoxia-inducible factor 1α (HIF-1α) and glucose transporter-1 (GLUT-1) are two important hypoxic markers associated with the radioresistance of cancers including laryngeal carcinoma. We evaluated whether the simultaneous inhibition of GLUT-1 and HIF-1α expression improved the radiosensitivity of laryngeal carcinoma. We explored whether the expression of HIF-1α and GLUT-1 was correlated with 2′-deoxy-2’-[18F]fluoro-D-glucose (18F-FDG) uptake and whether 18F-FDG positron emission tomography-computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 51 publications
3
29
1
Order By: Relevance
“…Glut-1 also affects cell proliferation and chemoradiotherapy sensitivity of head and neck squamous cell carcinoma, including laryngeal carcinoma13-18. Our previous studies suggested that Glut-1 may affect the proliferation, glucose uptake, chemosensitivity, and radiosensitivity [8,[13][14][15][16][17]. Although we found that the mechanism may be mediated through the PI3K/Akt pathway, the role of the activated PI3K/Akt pathway in this process was not significant.…”
Section: Introductioncontrasting
confidence: 71%
“…Glut-1 also affects cell proliferation and chemoradiotherapy sensitivity of head and neck squamous cell carcinoma, including laryngeal carcinoma13-18. Our previous studies suggested that Glut-1 may affect the proliferation, glucose uptake, chemosensitivity, and radiosensitivity [8,[13][14][15][16][17]. Although we found that the mechanism may be mediated through the PI3K/Akt pathway, the role of the activated PI3K/Akt pathway in this process was not significant.…”
Section: Introductioncontrasting
confidence: 71%
“…42 Inhibition of GLUT-1 may enhance the radiosensitivity of laryngeal carcinomas through decreasing microvessel density and promoting apoptosis and necrosis. 43 Activation of the PI3K/Akt pathway-mediated the trafficking and activity of GLUT-1 is positively associated with radioresistance. 44 In our previous study, we revealed that overexpression of GLUT-1-induced the radioresistance of laryngeal carcinoma was through activating PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although promising treatments preserving laryngeal function, including chemotherapy and radiotherapy, have been advanced, the overall survival rate of patients with laryngeal carcinoma remains poor. 1 , 2 One possible mechanism may be the development of chemoradioresistance in laryngeal carcinoma. Studies have demonstrated that hypoxia plays a key role in laryngeal carcinoma radioresistance: 3 6 1) Glucose transporter-1 (GLUT-1), as an important hypoxic marker, has also been found to have an important role in laryngeal carcinoma radiosensitivity, and inhibition of GLUT-1 expression may enhance the radiosensitivity of laryngeal carcinoma; 2 , 6 9 2) HIF-1α, as another important hypoxic marker, has also been found to have an important role in laryngeal carcinoma radiosensitivity, and inhibition of HIF-1α expression may enhance the radiosensitivity of laryngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%